2016
DOI: 10.1159/000458166
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus and the Development of Different Cancers

Abstract: Human papillomaviruses (HPV) are responsible for the development of almost all cervical cancers. HPV is also found in 85% of anal cancer and in 50% of penile, vulvar, and vaginal cancers, and they are increasingly found in a subset of head and neck cancers, i.e., oropharyngeal squamous cell carcinomas (OPSCC). The model for how HPV causes cancer is derived from several decades of study on cervical cancer, and it is just presumed that this model is not only completely valid for cervical cancer but for all other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 59 publications
(55 reference statements)
0
26
0
6
Order By: Relevance
“…The risk factors are represented by prior hysterectomy and human papilloma virus (HPV) infection [3][4][5]. The most common symptoms are discharge, bleeding and pain during sexual intercourse.…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors are represented by prior hysterectomy and human papilloma virus (HPV) infection [3][4][5]. The most common symptoms are discharge, bleeding and pain during sexual intercourse.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if the molecular profiles are different in the ASCC compared to the tongue and supraclavicular tumors, can one conclude that the tumors are clearly from separate tissues of origin? Gao and Smith reported that the molecular profile (using NGS) for "OPSCC appears distinct from cervical cancer" [6]. However, Koncar et al used immunohistochemistry and molecular profiling to study 743 p53 wild-type HPV-related cancers (including anal, OPSCC, cervical, and vulvar cancers) and concluded that "no gene had a statistically significant difference in mutation frequency or copy number between the four different types of squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In response to a report by the Joint Committee on Vaccination and Immunisation,1 Public Health England has initiated a pilot in which 42 genitourinary medicine and HIV clinics will provide the Gardasil vaccine to men who have sex with men (MSM). This pilot is supported by the evidence: MSM have a higher incidence of HPV than heterosexual men2 and the virus is linked to around 85% of anal cancers 3. Among the general population, however, it is also important to remember the burden of anal cancer among women.…”
mentioning
confidence: 86%